Acetogenic Fermentation From Oxygen Containing Waste Gas - Mohr, Teresa; Infantes, Alba; Biebinger, Lars; de Maayer, Pieter; Neumann, Anke (Frontiers in Bioengineering and Biotechnology, 2019)
The microbial production of bulk chemicals from waste gas is becoming a pertinent alternative to industrial strategies that rely on fossil fuels as substrate. Acetogens can use waste gas substrates or syngas (CO, CO2, H2) to produce chemicals such as acetate or ethanol, but as the feed gas often contains oxygen, which inhibits acetogen growth and product formation, a cost-prohibitive chemical oxygen removal step is necessary. Here, we have developed a two-phase microbial system to facilitate acetate production using a gas mixture containing CO and O2. In the first phase the facultative anaerobic carboxydotroph Parageobacillus thermoglucosidasius was used to consume residual O2 and produce H2 and CO2, which was subsequently utilized by the acetogen Clostridium ljungdahlii for the production of acetate. From a starting amount of 3.3 mmol of CO, 0.52 mmol acetate was produced in the second phase by C. ljungdahlii. In this set-up, the yield achieved was 0.16 mol acetate/mol CO, a 63 % of the theoretical maximum. This system has the potential to be developed for the production of a broad range of bulk chemicals from oxygen-containing waste gas by using P. thermoglucosidasius as an oxygen scrubbing tool.